2006
DOI: 10.3201/eid1205.050866
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegyptiLarval Indices and Risk for Dengue Epidemics

Abstract: Entomologic indices can identify areas at high risk for disease transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(194 citation statements)
references
References 34 publications
9
175
1
9
Order By: Relevance
“…This fi nding is in agreement with other studies that showed that the BI is an appropriate entomological index for use in low-infestation areas. 19,20 This result is in accordance with the fi ndings for Jaguare because this area's infestation level is low compared with those in some The main difference observed among the infestation maps in the geographical region evaluated was associated with the use of indices calculated per property or hectare. One reason for this difference is the presence of properties with large lots.…”
Section: Discussionsupporting
confidence: 85%
“…This fi nding is in agreement with other studies that showed that the BI is an appropriate entomological index for use in low-infestation areas. 19,20 This result is in accordance with the fi ndings for Jaguare because this area's infestation level is low compared with those in some The main difference observed among the infestation maps in the geographical region evaluated was associated with the use of indices calculated per property or hectare. One reason for this difference is the presence of properties with large lots.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with studies conducted in endemic Latin American cities, in which it has been shown that rainfall correlates positively with the larval population density of the vector and with the incidence of dengue. [41][42][43] Poverty has been identified as intrinsically related to the incidence of neglected tropical diseases such as dengue. Most of the countries with a low HDI and a greater burden of such diseases are located in tropical and subtropical regions.…”
Section: Determinants Of Dengue Mortalitymentioning
confidence: 99%
“…42 Eliminating vector breeding sites reduces vector density, a predictor of dengue infection risk. 43 In the case of Japanese encephalitis, the proximity of livestock reservoirs to irrigated areas can increase the risk of human infection. 44 Intermittent irrigation of rice paddy habitats and isolation of pig rearing from such areas can reduce the risk of infection.…”
Section: Vector-borne Infectionsmentioning
confidence: 99%